On intuitionistic fuzzy h-ideals in h-hemiregular hemirings and \( h^* \)-duo-hemirings - Sarwar, Muhammad; Ali, Majid (Eurasian Mathematical Journal, 2012)
In this paper, intuitionistic fuzzy h-bi-ideals and intuitionistic fuzzy h-quasi-ideals of hemirings are studied and some related properties are investigated. We characterize fully idempotent hemirings by the properties of their intuitionistic fuzzy h-ideals. We also characterize h-hemiregularity, h-intra-hemiregularity and h-quasi-hemiregularity in hemirings by the properties of their intuitionistic fuzzy h-bi-ideals and intuitionistic fuzzy h-quasi-ideals. The concept of intuitionistic fuzzy \( h^* \)-duo-hemirings is introduced and some of their characterizations are obtained.